ADAM10 Is Involved in Cell Junction Assembly in Early Porcine Embryo Development - Kwon, Jeongwoo (PLoS One, 2016)
ADAM10 (A Disintegrin and Metalloprotease domain-containing protein 10) is a cell surface protein with a unique structure possessing both potential adhesion and protease domains. However, the role of ADAM10 in preimplantation stage embryos is not clear. In this study, we examined the expression patterns and functional roles of ADAM10 in porcine parthenotes during preimplantation development. The transcription level of ADAM10 dramatically increased from the morula stage onward. Immunostaining revealed that ADAM10 was present in both the nucleus and cytoplasm in early cleavage stage embryos, and localized to the apical region of the outer cells in morula and blastocyst embryos. Knockdown (KD) of ADAM10 using double strand RNA did not alter preimplantation embryo development until morula stage, but resulted in significantly reduced development to blastocyst stage. Moreover, the KD blastocyst showed a decrease in gene expression of adherens and tight junction (AJ/TJ), and an increase in trophectoderm TJ permeability by disrupting TJ assembly. Treatment with an ADAM10 specific chemical inhibitor, GI254023X, at the morula stage also inhibited blastocyst development and led to disruption of TJ assembly. An in situ proximity ligation assay demonstrated direct interaction of ADAM10 with coxsackie virus and adenovirus receptor (CXADR), supporting the involvement of ADAM10 in TJ assembly. In conclusion, our findings strongly suggest that ADADM10 is important for blastocyst formation rather than compaction, particularly for TJ assembly and stabilization in preimplantation porcine parthenogenetic development.